search points attachment profile arrow left arrow right star heart verified symbols equation arrow-down question mark check menu accountancyadministrationagriculturalalgebraallarabicartart_musicbelarusbelarus_altbiologybusinesscatalachemistrychineseeconomicsegzamenglishentrepreneurshipenvironmentethicseuskarafirst_aidfrenchgalegogeographygeologygeometrygermangrammarhealthhistoryindia_langindonesian_langinformaticsitalianjapanesekazachkazach_altkoreanlanguagelatinlawlife_scienceliteraturelogicmathematicsmusicnigerian_langother_languagesotherspedagogicsphilosophyphysical_educationphysicspoliticspsychologyreligionrpa_langrussianrussian_altsciencesecurityskillssocial_sciencesociologyspanishstatisticstechnologytourismtrafficukrainianukrainian_altukrainian_literaturewos_civilisation accountancyadministrationagriculturalalgebraall_1arabicartart_music_2belarusbelarus_altbiologybusiness_2catalachemistry_1chineseeconomicsexam_3englishentrepreneurshipenvironment_2ethicseuskarasecurity_1frenchgalegogeography_4geology_4geometrygermangrammarhealthhistoryindia-langindonesian-langinformaticsitalianjapanesekazachAsset 230koreanlanguagelatinlawlife-scienceliteraturelogic_2mathematicsmusicnigerian-langotherlanguagesother_1pedagogicsphilosophyphysical_educationphysicspoliticspsychologyreligion_1rpa-langrussianrussian_altsciencesecurity_3_mskills_1allsocial_science_5_msociologyspanishstatisticstechnologytourismtrafficukrainianukrainian_altukrainian_literaturewos_civilisation

Ответ

Ответ дан
Nullpo201

1)

{x1-x2 = 5

{x1³-x2³ = 35

{x1-x2 = 5

{(x1-x2)(x1²+x1•x2+x2²) = 35

{x1 = 5+x2

{x1²+x1•x2+x2² = 7

(5+x2)²+x2(5+x2)+x2²-7 = 0

25+10x2+x2²+5x2+x2²+x2²-7 = 0

3x2²+15x2+18 = 0

x2²+5x2+6 = 0

По Виету:

[x2 = -2

[x2 = -3

[x1 = 5+x2 = 3

[x1 = 5+x2 = 2

(3; -2), (2; -3)

2)По виету

{x1+x2 = -p =3-2 = 1

{x1•x2 = q = -6

x²-x-6 = 0

3)По Виету:

{-p = x1+x2 = 2-3 = -1

{x1•x2 = q = -6

x²+x-6 = 0

Ответ

Ответ дан
mursalovasuriya

Ответ:

x1 - x2 = 5 \  {x}^{3} 1 -  {x}^{3} 2 = 35 \ (x1 - x2)( {x}^{2} 1 + x1x2 +  {x}^{2} 2) = 35 \  5({x}^{2} 1 + x1x2 +  {x}^{2} 2) = 35 \  {x}^{2} 1 + x1x2 +  {x}^{2} 2) = 7 \  {(x1 - x2)}^{2}  + 3x1x2 = 7 \ 25 + 3x1x2 = 7 \ 3x1x2 =  - 18 \ x1x2 =  - 6  \ x1x2 = q =  - 6 \ x1 =  frac{ - 6}{x2}  \  frac{ - 6}{x2}  - x2 = 5 \  - 6 -  {x}^{2} 2 = 5x2 \  {x}^{2} 2 + 5x2 + 6 = 0 \ x2 =  - 3 :  :  :  :  : x1 =  frac{ - 6}{ - 3}   = 2\ x2 =  - 2 :  :  :  : x1 =  frac{ - 6}{ - 2}  = 3  \  \ x1 + x2 =  - p1 = 2 + ( - 3) =  - 1 =  > p1 = 1 \ x1 + x2 =  - p2 = 3  + ( - 2) = 1 =  > p 2=  - 1

Ответы и объяснения

Не тот ответ, который тебе нужен?


По всем вопросам пишите на - vashurokk@rambler.ru